2021
DOI: 10.1038/s41380-021-01030-3
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and dissimilarities between psychiatric cluster disorders

Abstract: The common molecular mechanisms underlying psychiatric disorders are not well understood. Prior attempts to assess the pathological mechanisms responsible for psychiatric disorders have been limited by biased selection of comparable disorders, datasets/cohort availability, and challenges with data normalization. Here, using DisGeNET, a gene-disease associations database, we sought to expand such investigations in terms of number and types of diseases. In a top-down manner, we analyzed an unbiased cluster of 36… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…On the other, 24% of males receive a diagnosis of behavioral disorder compared to 8% of females. These percentages further confirm the results of previous studies, according to which internalizing disorders are more prevalent in females and, vice versa, externalizing disorders are more prevalent in males [8,43,44], as gender differences are linked to several different factors: genetic vulnerability, hormonal and neuropsychological changes, differences in personality, different coping styles, and cultural and social beliefs [43,45,46].…”
Section: Discussionsupporting
confidence: 88%
“…On the other, 24% of males receive a diagnosis of behavioral disorder compared to 8% of females. These percentages further confirm the results of previous studies, according to which internalizing disorders are more prevalent in females and, vice versa, externalizing disorders are more prevalent in males [8,43,44], as gender differences are linked to several different factors: genetic vulnerability, hormonal and neuropsychological changes, differences in personality, different coping styles, and cultural and social beliefs [43,45,46].…”
Section: Discussionsupporting
confidence: 88%
“…As the AGDS employed phenotyping across an extensive range of complex traits 104 , on balance it was not feasible to also collect detailed information from participants on dosages and (polypharmacy) combinations taken of the prescribed antidepressants 105 ; the duration and magnitude of benefits (e.g., for cost-effectiveness analyses) 66,106,107 ; drug tolerability and adverse events 66,108113 ; adjunct psychological therapies and multidisciplinary treatment/rehabilitation programs; 114 other prescribed pain pharmacotherapies and questionnaires. 115119 Further pharmacoepidemiological studies focusing on chronic pain and a large range of psychiatric comorbidities 51,52,120 can directly address and collect data on these specific issues. As the current data were based on self-reported responses, they may also be subject to a degree of participant recall bias (e.g., time-specific details).…”
Section: Discussionmentioning
confidence: 99%
“…To further assess differences in effectiveness between specific antidepressants, targeted interventional trials can directly address the other phenotypes not captured in the current study. Nevertheless, our large-scale data-driven approach — like recent human genetic 3652 and neuroimaging 5759 antidepressant treatment studies — have revealed novel insights into the relationship between chronic pain and depression. Along with animal model and human pharmacogenetic studies 5356,118,119,123127 , there is also independent converging evidence for the critical role of subcortical brain regions in mediating pain and mood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although each of these approaches are independent of the other, a multi-disciplinary omics study which aims to combine the results of each of these approaches may help to sort out the complex etiology of psychiatric disorders. Indeed, an integrative systems biology approach has been previously used for ASD (Briscoe & Marín, 2020;De Rubeis et al, 2014;Parikshak et al, 2015;Smail et al, 2021;Willsey et al, 2018).…”
mentioning
confidence: 99%